The Relative Price of Services. (20th December 2012) - Inklaar, Robert; Timmer, Marcel P.
<x xml:space="preserve">Abstract</x> Prices of GDP relative to the exchange rate increase with income per capita, which is known as the Penn‐effect. This is generally attributed to services being cheaper relative to goods in poorer countries. In this paper we re‐examine the Penn‐effect based on a new set of PPPs for industry output. These are estimated in an augmented Geary–Khamis approach using prices for final goods, exports, and imports. The resulting multilateral PPPs cover 35 industries in 42 countries for the year 2005. We find large variation in relative prices of various services industries. In particular the Penn‐effect appears to be mostly due to the rapidly rising output prices of non‐market services. This seems related mainly to the high labor intensity of that sector.